2011
DOI: 10.1007/s11258-011-9934-y
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of experimentally created gaps along an alpine successional gradient

Abstract: The colonization of artificially created gaps was analyzed along an alpine successional gradient from pioneer to early, late, and old successional stages. The presence/absence of species and the abundances of seedlings and adults in the gaps were recorded and compared with those of the surrounding areas. We hypothesized that in the older successional stages, the gaps were likely to be colonized by clonal ingrowth of the surrounding species. In the younger stages, we expected to find a high presence of seedling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 56 publications
4
24
0
Order By: Relevance
“…Vegetative ingrowth was therefore expected to contribute significantly to gap colonization. However, we documented vegetative ingrowth only later in the season, and it was always less common than the generative regeneration, which is consistent with other studies (Bullock et al 1995;Cichini et al 2011). Furthermore, clonal spread was confined mostly to the borders, and thus limited to short distances.…”
Section: Preferred Microsites and Environmental Conditionssupporting
confidence: 93%
“…Vegetative ingrowth was therefore expected to contribute significantly to gap colonization. However, we documented vegetative ingrowth only later in the season, and it was always less common than the generative regeneration, which is consistent with other studies (Bullock et al 1995;Cichini et al 2011). Furthermore, clonal spread was confined mostly to the borders, and thus limited to short distances.…”
Section: Preferred Microsites and Environmental Conditionssupporting
confidence: 93%
“…The contribution of plant species identity to goodness of fit for our mixed models was estimated by subtracting the goodness‐of‐fit r 2 for a model without species from the model with species. Statistical significance amongst the different species was obtained through formulating contrast statements within the same model structure, whilst controlling for multiple contrasts (see Hothorn et al ., ; Cichini et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…New Phytologist model without species from the model with species. Statistical significance amongst the different species was obtained through formulating contrast statements within the same model structure, whilst controlling for multiple contrasts (see Hothorn et al, 2008;Cichini et al, 2011).…”
Section: Researchmentioning
confidence: 99%
“…However, several studies reported of a general low seedling recruitment at early successional stages of glacier forelands (Marcante et al 2009b;Niederfriniger Schlag and Erschbamer 2000;Stöcklin and BĂ€umler 1996), but more experimental studies are needed that explicitly address the relationship of seed mass, germination and survival of glacier foreland species. Limitation of seedling recruitment also plays a role in later successional stages, but abundant litter Table 1 and high canopy cover are assumed to be the main causes of low recruitment at these sites (Cichini et al 2011;Marcante et al 2009b). Thus, heavier seeds should also be advantageous for seedling recruitment in later successional stages as reported from other communities with prevailing competitive grasses (Jacobsson and Eriksson 2000).…”
Section: Seed Mass: a Plant Trait Shaped By Trade-offsmentioning
confidence: 86%